East Africa: Tanzania - Agriculture, food security and climate change outlook - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Agriculture contributes approximately 32% to the country’s GDP in 2015, mostly through food crop production, which accounted for approximately 65% of the agricultural GDP. Nearly 60% of of the economically active population is employed in the sector. Women make up roughly half of the workforce and produce more than 70% of the country’s food. Approximately 7.2 million youth make a living from agriculture. Low productivity has been linked to a combination of several factors, including: overreliance on rainfall, utilization of rudimentary and unsustainable production methods, poor access to inputs, and low extension service capacity to deal with climate change issues. These factors challenge the ability to adapt and build community resilience to climate change, food and nutrition security and the efforts of the country to improve mitigation co-benefits in line with national economic development priorities.